AFTER JIHAD: Transformation of Radicalism and Verbatim Prejudice Among Ex-Convicts in the "Red Zone" of Terrorism in Bima-Dompu, East Indonesia - Hendrawangsyah Hendrawangsyah; Abdul Malik; Syed Hadzarullathfi Bim Syed Omar; Syafira Anisatul Izah; Lutfatul Azizah (SANGKÃ©P: Jurnal Kajian Sosial Keagamaan, 2023)
This article aims to re-investigate the Jihad movement of ex-terrorist convicts among the caregivers and teachers of the as-Salam Tahfidzul Quran Islamic boarding school in the Red Zone area of Bima-Dompu, Eastern Indonesia. This article focuses on two things by using a phenomenological qualitative approach, namely: (1) investigating the Jihad movement transformation of the ex-terrorist convicts among as-Salam Tahfidz Quran Islamic boarding school caretakers/teachers, (2) examining negative prejudice against as-Salam Tahfidzul Quran Islamic boarding school as "Terrorist School". The data in this article were collected using observation, participation, interview and documentation techniques which are analyzed inductively. The fieldwork on the study of religious movements in this article shows two significant results. First, the understanding and movement of Jihad for the ex-terrorist convicts among the caretakers/teachers of as-Salam Tahfidzul Quran Bima-Dompu Islamic Boarding School has changed and transformed Jihad from "taking up arms" to "Amar Makruf Nahi Mungkar" which pursued through education. Second, the increment of highly negative prejudice towardsÂ  As-Salam Tahfidzul Quran Bima-Dompu Islamic Boarding School as a "Terrorist School" among the large community due to the lack of communication from the government to the community regarding the developments of the ex-convicts and the safety assurance of them being in the community after they have served their prison term. Through a significant academic analysis, this article draws a temporary conclusion that Bima-Dompu NTB is no longer a terrorist Red Zone area.